Applied Mathematics Analysis of the Multibody Systems - TAÇGIN, ERTUĞRUL (AMER INST PHYSICS, 2012)
A methodology is developed for the analysis of the multibody systems that is applied on the vehicle as a case study. The previous study emphasizes the derivation of the multibody dynamics equations of motion for bogie [2]. In this work, we have developed a guide-way for the analysis of the dynamical behavior of the multibody systems for mainly validation, verification of the realistic mathematical model and partly for the design of the alternative optimum vehicle parameters.
Keywords: Multibody; Eigenvalue; Analysis; Mechatronics; Dynamics; Symbolic Mathematics; Differential-Algebraic Equations (DAEs); Equations of Motion (EOM); Railway Vehicle; Bogie; Trajectory Coordinate; Lagrange Dynamics